India: The funding and organization of Agricultural R&D-evolution and emerging policy issues - Pal, Suresh; Byerlee, Derek (International Food Policy Research Institute, 2006)
India has one of the largest and most complex agricultural research systems in the world, with more than a century of organized application of science to agriculture. A proactive policy by the government toward agricultural research and education (R&E) coupled with support from a number of bilateral and multilateral donors, has produced an institutionally diverse research system that has achieved many successes, most notably the Green Revolution in the 1960s and 1970s. The country is not only self-sufficient in food but also commands a strong position in world markets for some commodities. Many studies have empirically shown the impressive performance of the system, with annual rates of return to investment in research ranging from 35 to 155 percent (Evenson, Pray, and Rosegrant 1999). Notwithstanding these achievements, the system must now address a more complex and expanding research agenda of sustaining natural resources, enhancing product quality, and ensuring food safety, in addition to increasing household food and nutritional security and reducing poverty. These new challenges require a rematching of needs with resources, and a reorientation of R&E policy.